2008
DOI: 10.1620/tjem.215.307
|View full text |Cite
|
Sign up to set email alerts
|

A Patient with Focal Fibrocartilaginous Dysplasia in the Distal Femur and Review of the Literature

Abstract: Focal fibrocartilaginous dysplasia (FFCD) is a rare and benign bone lesion that induces bowing deformity of the long bones in young children. Excessive production of fibrocartilage by abnormal differentiation in the metaphysis or by trauma during delivery or after birth is thought to cause growth disturbance. Radiologically, the lesion is characterized by a lucent defect with marginal sclerosis in the medial metaphysis of the long bone. However, there have been few reports about the initial radiological change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Ando et al [7] reported 89 cases of FFCD from 1985 to 2007, and 54 (61%) of these were located in the proximal medial tibia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ando et al [7] reported 89 cases of FFCD from 1985 to 2007, and 54 (61%) of these were located in the proximal medial tibia.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are some opinions on the origin of the pathology, the common understanding that has emerged recently is that FFCD is characterized by abnormal development of fibrocartilage at the site of tendon insertion, which prevents natural sliding of the periosteum of the metaphysis and diaphysis during growth [7,12].…”
Section: Etiologymentioning
confidence: 99%
See 1 more Smart Citation
“…16,23,24 It has also been reported at several other sites. This includes the distal femur (18 cases), [25][26][27][28][29][30][31] ulna (16 cases), 3,[32][33][34][35][36] humerus (four cases), 32,37 radius (two cases) 33 and phalanx (two cases), 33 but never in the proximal femur.…”
Section: Figure 4 Short Tau Inversion Recovery (Stir) Mri Showing Thmentioning
confidence: 99%
“…The tethering effect of the fibrous band causes a hemiepiphysiodesis effect and results in angular deformities as well as limb-length discrepancies of long bones ( 4 , 5 ). Patients are mostly diagnosed with varus or valgus malalignment of the lower extremities at the age of 12–24 months ( 6 ).…”
Section: Introductionmentioning
confidence: 99%